NOVEL ANTICOAGULANTS FOR THROMBOEMBOLIC COMPLICATIONS PREVENTION IN NONVALVULAR ATRIAL FIBRILLATION - D. A. Itkin; Yu. N. Moiseeva; I. A. Libov (Российский кардиологический журнал)
The article takes into consideration practical issues of novel oral anticoagulants (factor Xa inhibitors) usage with the aim of prevention of thromboembolic complications in nonvalvular atrial fibrillation.A clinical case presented the patient with this pathology under high risk of thromboembolic complications with several years follow-up.